Schweinfurthin natural products induce regression of murine melanoma and pair with anti-PD-1 therapy to facilitate durable tumor immunity. (1st February 2019) - Kokolus, Kathleen M.; Haley, Jeremy S.; Koubek, Emily J.; Gowda, Raghavendra; Dinavahi, Saketh S.; Sharma, Arati; Claxton, David F.; Helm, Klaus F.; Drabick, Joseph J.; Robertson, Gavin P.; Neighbors, Jeffrey D.; Hohl, Raymond J.; et al.
ABSTRACT: Metastatic melanoma is a significant clinical problem with a 5-year survival rate of only 15–20%. Recent approval of new immunotherapies and targeted inhibitors have provided much needed options for these patients, in some cases promoting dramatic disease regressions. In particular, antibody-based therapies that block the PD-1/PD-L1 checkpoint inhibitory pathway have achieved an increased overall response rate in metastatic melanoma, yet durable response rates are reported only around 15%. To improve the overall and durable response rates for advanced-stage melanoma, combined targeted and immune-based therapies are under investigation. Here, we investigated how the natural products called schweinfurthins, which have selective anti-proliferative activity against many cancer types, impact anti-(α)PD-1-mediated immunotherapy of murine melanomas. Two different compounds efficiently reduced the growth of human and murine melanoma cells in vitro and induced plasma membrane surface localization of the ER-resident protein calreticulin in B16.F10 melanoma cells, an indicator of immunogenic cell death. In addition, both compounds improved αPD-1-mediated immunotherapy of established tumors in immunocompetent C57BL/6 mice either by delaying tumor progression or resulting in complete tumor regression. Improved immunotherapy was accomplished following only a 5-day course of schweinfurthin, which was associated with initial tumor regression even in the absence of αPD-1. Schweinfurthin-induced tumor regression required an intact immune system as tumors were unaffected in NOD scid gamma (NSG) mice. These results indicate that schweinfurthins improve αPD-1 therapy, leading to enhanced and durable anti-tumor immunity and support the translation of this novel approach to further improve response rates for metastatic melanoma.